Paladino : Veroniche - Testori, Giovanni (Brussel : Artiscope, 1989)
Art book published on the occasion of the "Veroniche" exhibition by Mimmo Paladino at the Saint-Augustin Church in Brussels from December 1989 to January 1990. Text « I lini della Veronica » by Giovanni Testori. 18 pages on water-colour paper with red hand-tinted page borders; 7 color reproductions; dimensions cm. 50 x 26; hardcover in cardboard and gauze. Design by Mimmo Paladino. Published in a limited edition of 500 numbered copies by Artiscope, Brussels in 1989
Italiaans
boek
Keywords: Paladino, Mimmo